Lead adsorption in clay and its application (2012)
"This work presents the adsorption capacities of some heavy metals in clay soil and its application in medical field. Nitrate of lead solution of different concentrations were prepared (400ppm, 800ppm… 6400ppm). Each concentration of lead nitrate solutions was mixed with a known volume of clay. Slabs of regular dimensions were formed from the residue after it had gone through filtration. Each slab (dried) was irradiated with x-ray radiation at different energies; 40kev, 60kev, 80kev,100kev and 120kev. Linear and mass attenuation of each slab were determined. We did this in order to check shielding ability of the adsorption capacities of heavy metals in clay soil. The research works on clay soil used mainly in building construction and pot making. A PTM UNIDOS electrometer at National Institute of Radiation Protection Research (NIRPR), University of Ibadan, was used to record the counting .A Graph of logarithm of incident intensity versus logarithm of transmitted intensity was plotted to calculate mass attenuation of the slabs at different concentrations. An Atomic Absorption Spectrometer (AAS) was used in analyzing the concentration of heavy metals present in each sample. The results obtained from X-ray Photoelectron Spectroscopy (XPS) show that attenuation coefficient decreases as the radiation energy increases. The linear correlation coefficient between the concentration of heavy metals and attenuation coefficient was approximately 1. "